In vitro reduction of methane production by 3-nitro-1-propionic acid is dose-dependent1. (10th January 2019) - Ochoa-García, Pedro Antonio; Arevalos-Sánchez, Martha María; Ruiz-Barrera, Oscar; Anderson, Robin C; Maynez-Pérez, Adrián Omar; Rodríguez-Almeida, Felipe A; Chávez-Martínez, América; Gutiérrez-Bañuelos, Héctor; Corral-Luna, Agustín
Abstract: Methanogenesis is a metabolic process that allows the rumen ecosystem the ability to maintain the low hydrogen partial pressures needed for proper digestive function. However, rumen methanogenesis is considered to be an inefficient process because it can result in the loss of 4% to 12% of the total energy consumed by the host. Recent studies have shown that some short-chain nitrocompounds such as nitroethane, 2-nitroethanol, 2-nitro-1-propanol, and 3-nitro-1-propionic acid (3NPA ) are capable of inhibiting the production of methane during in vitro culture; nevertheless, optimal supplementation doses have yet to be determined. In the present study, in vitro cultures of freshly collected mixed populations of ruminal microbes were supplemented with the naturally occurring nitrocompound, 3NPA, to achieve 0, 3, 6, 9, or 12 mM. Analysis of fermentation products after 24 h of incubation revealed that methane (CH 4 ) production was reduced in a dose-dependent manner by 29% to 96% ( P < 0.05) compared with the amount produced by untreated controls (15.03 ± 0.88 µmol mL −1 incubated liquid). Main effects of the supplement were also observed, which resulted in a reduction ( P < 0.05) on amounts of total gas and volatile fatty acids (VFA) produced, as well as in an increase of 0.07 to 0.30 µmol mL −1 on rates of 3NPA degradation. Changes in production of metabolites as CH4, hydrogen (H 2 ), VFA, and NH3 indicated that the fermentation efficiency was not compromised dramatically by 3NPA treatment in moderate doses of 6 and 9 mM. Results further revealed that the metabolism of the 3NPA by microbial populations is also dose-dependent. The microbes were able to metabolize more than 75% of the added nitrocompound, with the greatest degradation rates in cultures treated with 9-mM 3NPA. Finally, from a practical standpoint, and considering the magnitude of CH4 reduction, effect on VFA, and percentage of metabolized supplement, the most efficacious dose for 3NPA administration may be between 3 and 9 mM.